(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2017)
The volume of data organizations and government agencies usually collect and store are increasing rapidly. Centralized database according to Elmasri and Navathe [1] stores data or information in a particular location within a network. It allows data from existing database to be collected and stored in a single database for sharing, analysis or updating in an organisation. In Nigeria, organizations and government agencies usually operates distributed databases and do not have a centralised database in a central location for sharing and other policy making. Therefore, this paper highlights the need for centralised database that can be adopted by government to control data redundancy and inconsistency for security and sustainable development. The paper is a survey paper that explored the use of research schedules for data collection. Enumeratorwas picked from each of the four agencies that constitutes the population and samples of the study. The data collected were categorised and presented based on the research schedules retrieved. The results show the common fields used on personal information of individuals as ID, names, Date of Birth, Gender, address, phone no, finger print, and photograph. The results also show that data sharing among agencies are rarely done using the distributed databases, but plans are on the way to actualize that especially with the yet-to-be implemented model of National Identity Management Commission known as National Identity Management System (NIMS). Finally, the paper recommends that government should explore the possibility of adopting centralised database that can harmonise records of organisations and agencieswhich will help in ensuring security and sustainable development in the country; a model of centralised database should be designed to ascertain the feasibility of implementing a centralised database in Nigeria; thorough research should also be made to ensure the compatibility between organisations and agencies with the centralised database for data sharing and other accessibility issues.